Enhancing the Behavior of One-Way Reinforced Concrete Slabs by Using Laced Reinforcement - Ali Faiq Hallawi; Ali Hussein Ali Al-Ahmed (Salehan Institute of Higher Education, 2019)
This paper studies experimentally the behavior of laced reinforced concrete one-way slabs under monotonic load. The experimental program included testing three simply supported one-way slabs of dimensions (1500 mm length, 600 mm width, and thickness 130mm. One of these slabs was the control specimen which was designed without lacing reinforcement steel and the other two specimens designed were with two variable lacing reinforcement ratio (0.27% and 0.52%). All specimens were cast with normal of 22 MPa compressive strength. Specimens were tested under two equal line loads applied at the third parts of the slab (monotonic load) gradually applying up to failure. The specimens showed an enhanced in ultimate load capacity up to 40% as a result of increasing the lacing steel ratio to 0.52 %. Also, decreasing in deflection at service and at ultimate load levels by 42% and %57 respectively. In addition, the results showed that specimen with lacing reinforcement are more ductility than specimen without lacing reinforcement so using of lacing steel reinforcement leads to significant improvements in ductility index which reached to about 49% with increasing the lacing steel ratio to (0.52%).